Efforts To Improve the Quality of Welding Plastic Pallet Type HDX1210R With Six Sigma Method at PT. Pallets - Jaya, Mochamad Alfi Septian; Misbah, Achmad (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
PT. Pallets is a manufacturing company that processes plastic waste into products that have value, namely plastic pallets. A plastic pallet is a flat city-shaped container used as a base for storing and transporting goods in logistics warehousing. This study aims to improve the quality of plastic pallet welding products of the HDX1210R type at PT. Pallets. This study uses the Six Sigma method with the DMAIC (Define - Measure - Analyze - Improve - Control) approach with the help of fishbone diagrams, Pareto diagrams, and FMEA. From the company's historical data from March 2022 to March 2023, 3 types of defects were obtained, with loose welding as the highest type of defect, with a percentage of 89% of the total product defects. The overall DPMO average value is 49908.1405, and the average sigma value is 3.191. From FMEA calculations, the highest RPN value is obtained for frequently changing over machines with a scale value of 480. The proposed improvements can be made by changing the hitter model and size, modifying the mold (pallet molding) by adding the welding area on the pallet and making SOPs for producing HDX1210R-type pallet welding.